1988
DOI: 10.1143/jjap.27.2107
|View full text |Cite
|
Sign up to set email alerts
|

DLTS Study for Energy-Broadening of the Defect Level on Introducing Radiation Damage in GaP

Abstract: Measurements of deep-level transient spectroscopy (DLTS) have been made on the n-GaP before and after electron irradiation at 10 MeV. The density of an electron trap with an activation energy of 0.38 eV, which originally exists in the as-grown crystal, is reduced by the irradiation at an average reduction rate of 0.07 cm-1. The DLTS spectrum for this trap is broadened with irradiation and sharpened with successive annealing. The level broadening ΔE t of the trap is estimated by the simulation… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1989
1989
2009
2009

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(2 citation statements)
references
References 12 publications
0
2
0
Order By: Relevance
“…It was found that the transients could be modeled well by assuming that the levels were broadened. Endo et al (15) showed that broadening of levels can occur as a result of potential fluctuations in the bulk. These fluctuations may be screened out at higher temperatures by the increased carrier density.…”
Section: Discussionmentioning
confidence: 99%
“…It was found that the transients could be modeled well by assuming that the levels were broadened. Endo et al (15) showed that broadening of levels can occur as a result of potential fluctuations in the bulk. These fluctuations may be screened out at higher temperatures by the increased carrier density.…”
Section: Discussionmentioning
confidence: 99%
“…The researches of structural defects in GaP monocrystals, which started at the end of 60-ths, are still far from the completion. The number of published works concerning these problems increases rapidly; many of them deal with radiation-induced lattice defects [1][2][3][4][5][6][7][8][9].…”
Section: Introductionmentioning
confidence: 99%